Shear strengthening of reinforced concrete beams using epoxy bonded steel plates, CFRP sheets and externally anchored stirrups - Minh, Ha; Mutsuyoshi, Hiroshi (Vietnam Journal of Mechanics, 2008)
This research presents the effectiveness of different shear strengthening methods using epoxy bonded steel plates, steel strips, carbon fiber reinforced plastics (CFRP) sheets and externally anchored stirrups for enhancing the shear strength of RC beams. In this study, an experimental program including two series of twelve specimens was carried out to investigate the behavior of RC beams strengthened with the above methods. Further, a numerical analysis using finite element method (FEM) was performed to simulate the behavior of strengthened beams. The effectiveness of using epoxy bonded steel plates, CFRP sheets and externally anchored stirrups for shear strengthening of RC beams is confirmed through both numerical and experimental results.